2016
DOI: 10.1002/ange.201605091
|View full text |Cite
|
Sign up to set email alerts
|

Reagent‐Controlled α‐Selective Dehydrative Glycosylation of 2,6‐Dideoxy‐ and 2,3,6‐Trideoxy Sugars

Abstract: We have found that activating either 2,3-bis(2,3,4trimethoxyphenyl)cyclopropenone or 2,3-bis(2,3,4-trimethoxyphenyl)cyclopropene-1-thione with oxalyl bromide results in the formation of as pecies that promotes the glycosylation between 2,6-dideoxy-sugar hemiacetals and glycosyl acceptors in good yield and high a-selectivity.B oth reactions are mild and tolerate anumber of sensitive functional groups including highly acid-labile 2,3,6-trideoxy-sugar linkages.Supportinginformation and the ORCID identification nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…A major challenge with the synthesis of deoxy-glycosides is controlling the selectivity in glycosylation reactions with deoxy-sugar donors. This is due to both their increased reactivity and lack of functionality for appending directing groups on the donor that can bias the selectivity of glycosylation reactions. , In recent years this has led several research groups to examine new methods for the stereoselective construction of 2-deoxy glycosides. Our own group has had a longstanding interest in developing glycosylation methodologies for deoxy glycoside synthesis wherein the stereochemical outcome of the reaction is determined by the promoter. Most recently, we have demonstrated that either tosyl chloride or triisopropyl­benzene­sulfonyl chloride (Trisyl chloride) can efficiently activate deoxy-sugar hemiacetals for highly selective glycosylation reactions with a number of 2,6-dideoxy- and 2,3,6-trideoxy-sugar donors . Having established that this chemistry was useful for the construction of disaccharide linkages, we sought to determine its utility in the synthesis of more complex oligosaccharides.…”
mentioning
confidence: 99%
“…A major challenge with the synthesis of deoxy-glycosides is controlling the selectivity in glycosylation reactions with deoxy-sugar donors. This is due to both their increased reactivity and lack of functionality for appending directing groups on the donor that can bias the selectivity of glycosylation reactions. , In recent years this has led several research groups to examine new methods for the stereoselective construction of 2-deoxy glycosides. Our own group has had a longstanding interest in developing glycosylation methodologies for deoxy glycoside synthesis wherein the stereochemical outcome of the reaction is determined by the promoter. Most recently, we have demonstrated that either tosyl chloride or triisopropyl­benzene­sulfonyl chloride (Trisyl chloride) can efficiently activate deoxy-sugar hemiacetals for highly selective glycosylation reactions with a number of 2,6-dideoxy- and 2,3,6-trideoxy-sugar donors . Having established that this chemistry was useful for the construction of disaccharide linkages, we sought to determine its utility in the synthesis of more complex oligosaccharides.…”
mentioning
confidence: 99%
“…In certain cases, generation of highly reactive glycosyl donors in situ could improve the yield of stagnant glycosylations, as demonstrated in the coupling of ceramide acceptors with trimethylsilyl iodide donors generated in situ 25g and α-selective glycosylation with 2deoxysugar donors via in situ generated bromide donors using cyclopropenone-(and cyclopropene-1-thione-)-derived promoters. 17 Methods for the selective protection of monosaccharide building blocks are based on the well-established differences in the intrinsic reactivities of the hydroxyl groups. 27 While orthogonally protected sugars are still at the core of chemical synthesis, 27b various methodologies for glycosylation of unprotected donors and acceptors have emerged.…”
Section: Among Manymentioning
confidence: 99%